Pulmonary bioassay studies with brake lining components - Nonfibrous potassium octatitanate - Terracess JS particles in rats. (July 2021) - Warheit, David B.; Levy, Leonard S.
Abstract: Nonfibrous potassium octatitanate particles are commercially utilized in applications such as brake pads or brake linings. The aim of this study was to assess lung toxicity in rats exposed to Terracess JS particle-types, one form of nonfibrous octatitanate particulates, and compare the effects to vehicle controls and to Min-U-Sil α-quartz particles as a positive benchmark control particle. Groups of male rats were intratracheally instilled with doses of either 1 or 5 mg/kg of Terracess JS particles or α-quartz particles in phosphate-buffered saline. Phosphate-buffered saline (PBS) solution instilled rats served as vehicle controls. Following exposures, the lungs of PBS and particle-exposed rats were evaluated for bronchoalveolar lavage (BAL) fluid inflammatory biomarkers at post-instillation time points of 1 week, 1 month, and 3 months. In addition, lung tissue morphologies from PBS or 5 mg/kg particle-exposed (Terracess JS or α-quartz) rats were evaluated at postexposure time points of 1 month and 3 months. The BAL fluid results demonstrated that pulmonary instillation exposures in rats to quartz particles produced sustained pulmonary inflammation and significant cytotoxic effects measured at 1 week, 1 month and 3 months postexposure. In contrast, exposures to Terracess JS particle-types produced no significant lung inflammatory or cell injury effects when compared to PBS vehicle control exposed rats. With regard to histopathology of lung tissue, pulmonary exposures to quartz particles in rats produced a progressive, dose-dependent lung inflammatory response characterized by neutrophils and foamy lipid-containing alveolar macrophage accumulation, as well as evidence of early lung tissue thickening consistent with the development of pulmonary fibrosis at the 3-month postexposure time period. In contrast, histopathological analyses of lung tissues revealed that pulmonary exposures to Terracess JS particulates resulted in no significant adverse effects when compared to PBS-exposed controls, as evidenced by the normal lung architecture observed in the exposed animals at post-instillation exposure time periods ranging from 1 month to 3 months. The results described herein demonstrate the benign nature of the pulmonary instillation response in rats following particle exposures to 1 or 5 mg/kg (approximately 1.25 mg) of Terracess JS particle-types in these pulmonary bioassay studies, using appropriate benchmark control particles for comparative evaluations. Thus, based on these results, it is concluded that inhaled Terracess JS particles are expected to have a low-risk potential for producing adverse pulmonary health effects in exposed workers. Highlights: We investigated the pulmonary impacts of exposure to brake pad particulates. This study assessed in rats the lung toxicity of nonfibrous potassium titanate particles utilized in brake pads. Rats were intratracheally exposed at 2 different doses of potassium titanate or quartz (positive control) particles. Lung evaluation was implemented via bronchoalveolar lavage and histopathology at 2-3 postexposure time periods. The results from titanate particle-exposed rats were not significantly different from PBS-exposed control rats.